230 Boston Scientific vs. Coloplast: A Prospective Analysis of a Single High-volume Surgeon's Inflatable Penile Prosthesis Experience. Issue 1 (1st April 2022) - Lopez, J; Bansal, U; Brunner, R; Luna, E; Khera, M; Gheiler, E
ABSTRACT: Introduction: Surgical implantation of a penile prosthesis may be offered to patients with erectile dysfunction (ED) as primary treatment or after failed therapy. The two FDA approved three-piece inflatable penile prostheses (IPPs) on the market, the AMS (American Medical Systems) 700TM series (Boston Scientific, Massachusetts) and the Coloplast Titan® (Coloplast, Minnesota), differ in their overall design and anti-microbial coating. However, little is known as to whether these differences have an impact on risk of infection or revision. Objective: To compare the likelihood of infection and short-term revision in IPP placements performed by a single high-volume surgeon when using Boston Scientific's AMS 700TM series versus Coloplast Titan® implants. Methods: We performed a prospective analysis of a single IPP surgeon's experience with AMS 700TM and Titan® at two private hospitals between January 2017 and December 2019. The surgeon alternated the implants every other week for comparison. Data was collected on patient demographics, implant characteristics, case duration, and complications. Results: A total of 542 patients (mean age 69.2 years) underwent 548 IPP implantations during the two-year period. Of the 548 cases, 303 (55.3%) implantations were performed using Boston Scientific AMS 700TM while 245 (44.7%) were with Coloplast Titan®. Only one (0.18%) case was complicated by post-operative infection despite drain placement for three days in all 548 cases. This infection occurred in a Coloplast Titan® placed as a revision for SST deformity. Seven (1.3%) cases ultimately required revision by the time of review. Although five of the seven cases requiring revision were done using AMS 700TM implants, this did not amount to a statistically significant increase in risk compared to Titan® (p=0.39). First revisions of AMS 700TM were noted to be done earlier than Titan® on average (225 days vs. 450 days postoperatively, p=0.42). Overall, the most common reason for revision was tube fracture (n=3). Diabetes, case time, performing hospital, reservoir type, and reservoir location were not significant prognostic factors for revision (p>0.05). Conclusions: Risk of infection or short-term revision is not impacted by whether the IPP is manufactured by Coloplast or Boston Scientific. A high-volume IPP surgeon has a significantly decreased risk of infection and revision compared to those currently published in the literature. Disclosure: No